Neonatal transitional support with intact umbilical cord in assisted vaginal deliveries: a quality-improvement cohort study - Elisabeth Sæther; Friedrich Reinhart-Van Gülpen; Christer Jensen; Tor Åge Myklebust; Beate Horsberg Eriksen (BMC, 2020)
Abstract Background Deferring cord clamping has proven benefits for both term and preterm infants, and recent studies have demonstrated better cardio-respiratory stability if clamping is based on the infant's physiology, and whether the infant has breathed. Nevertheless, current guidelines for neonatal resuscitation still recommend early cord clamping (ECC) for compromised babies, unless equipment and competent personnel to resuscitate the baby are available at the mother's bedside. The objective of this quality improvement cohort study was to evaluate whether implementing a new delivery room protocol involving mobile resuscitation equipment (LifeStart™) reduced the prevalence of ECC in assisted vaginal deliveries. Methods Data on cord clamping and transitional care were collected 8 months before and 8 months after implementing the new protocol. The Model for Improvement was applied to identify drivers and obstacles to practice change. Statistical Process Control analysis was used to demonstrate signals of improvement, and whether these changes were sustainable. Multivariate logistic regression was used to evaluate the impact of the new protocol on the primary outcome, adjusted for possible confounders. Results Overall prevalence of ECC dropped from 13 to 1% (P < 0.01), with a 98% relative risk reduction for infants needing transitional support on a resuscitation table (adjusted OR 0.02, P < 0.001). Mean cord clamping time increased by 43% (p < 0.001). Although fewer infants were placed directly on mothers' chest (n = 43 [42%] vs n = 69 [75.0%], P < 0.001), there were no significant differences in needs for immediate transitional care or transfers to Neonatal Intensive Care Unit. A pattern of improvement was seen already before the intervention, especially after mandatory educational sessions and cross-professional simulation training. Conclusions A new delivery-room protocol involving mobile resuscitation equipment successfully eliminated early cord clamping in assisted vaginal deliveries of term and near-term infants. A systematic approach, like the Model for Improvement, seemed crucial for both achieving and sustaining the desired results. Trial registration The study was approved as a service evaluation as defined by the Regional Committee for Medical and Health Research Ethics ( 2018/1755/REK midt ).